Functionalization of bone implants with nanodiamond particles and angiopoietin-1 to improve vascularization and bone regeneration12. Issue 32 (19th June 2017) - Wu, Xujun; Bruschi, Michela; Waag, Thilo; Schweeberg, Sarah; Tian, Yuan; Meinhardt, Thomas; Stigler, Robert; Larsson, Karin; Funk, Martin; Steinmüller-Nethl, Doris; Rasse, Michael; Krueger, Anke
Abstract : Biodegradable β-TCP implant materials functionalized with diamond nanoparticles are generated and characterized. Abstract : One of the major challenges in bone tissue engineering is adequate vascularization within bone substituents for nutrients and oxygen supply. In this study, the production and results of a new, highly functional bone construct consisting of a commercial three-dimensional β-tricalcium phosphate scaffold (β-TCP, ChronOS®) and hydrophilic, functionalized nanodiamond (ND) particles are reported. A 30-fold increase in the active surface area of the ChronOS + ND scaffold was achieved after modification with ND. In addition, immobilization of angiopoietin-1 (Ang-1) via physisorption within the β-TCP + ND scaffold retained the bioactivity of the growth factor. Homogeneous distribution of the ND and Ang-1 within the core of the three-dimensional scaffold was confirmed using ND covalently labelled with Oregon Green. The biological responses of the β-TCP + ND scaffold with and without Ang-1 were studied in a sheep calvaria critical size defect model showing that the β-TCP + ND scaffold improved the blood vessel ingrowth and the β-TCP + ND + ND + Ang-1 scaffold further promoted vascularization and new bone formation. The results demonstrate that the modification of scaffolds with tailored diamond nanoparticles is a valuable method for improving the characteristics of bone implants and enables new approaches in bone tissue engineering.